The Changing Paradigm of Debt - Kathryn R. Heidt (Washington University Law Quarterly, 1994)
In this Article I suggest that the current paradigm of debt used in bankruptcy law is outmoded. Products liability and mass tort bankruptcies were the first wave of cases with obligations that did not fit neatly into the existing model of debt. Environmental obligations were next-obligations based on Superfund and other federal and state environmental laws.
Keywords: Bankruptcy law; Debtor and creditor; United States; Bankruptcy claims